Digital Transformation in Enhancing Operational Efficiency of E-Commerce Platforms in Southeast Asia: A Comprehensive Analysis and Strategic Implications - Putra, Johni Eka (Asosiasi Peneliti dan Inovasi Nusantara (APIN), 2025)
This study explores the role of digital transformation in enhancing operational efficiency across e-commerce platforms in Southeast Asia. Through a systematic literature review of 50 academic and industry sources, the research examines the adoption of digital technologies such as artificial intelligence (AI), Internet of Things (IoT), blockchain, and big data and their impact on logistics, customer experience, and performance outcomes. Using the Technology-Organization-Environment (TOE) framework as a conceptual lens, the study thematically analyzes key digital capabilities and their strategic implications, particularly for small and medium enterprises (SMEs). Findings suggest that digital transformation contributes to cost efficiency, service responsiveness, and process integration, with AI alone estimated to reduce operational costs by 15%-20% in leading platforms. While prior studies often focus on isolated technologies or single-country contexts, this research provides a cross-country synthesis that highlights common trends, challenges, and enabling factors. This study fills a critical gap in the literature by offering an integrated regional perspective on how bundled digital technologies shape operational strategies across diverse e-commerce ecosystems. The insights generated serve as a strategic reference for digital policy development, infrastructure investment, and organizational transformation in Southeast Asia.